О методике комплексной оценки особенностей личности горнорабочих и определения их профессиональной пригодности - Присняков, В.Ф.; Кияшко, Ю.И.; Шевченко, В.Г.; Присняков, К.В. (Геотехническая механика, 2010)
Викладено основні положення методики комплексної оцінки особливостей особистості
гірників і визначення їхньої професійної придатності. Приведено приклади використання методики. The main rules of a methodic of a complex estimation of features of the person of
the colliers and definition of their professional suitability are set up. The examples of
usage of a methodic are adduced.